Characterization of High Protein and Instant Cereal Fiber Drink Enriched with Probiotic Milk Powder - Tanuwijaya, Shania Angeline; Fibri, Dwi Larasatie Nur; Rahayu, Endang Sutriswati; Yanti, Rini; Saputra, Wahyu Dwi (agriTECH, 2025)
An alternate healthy snack for school-age children can be prepared by adding sorghum and tempeh flour, which are sources of protein and fiber, to instant cereal drinks. Probiotic-enriched snacks are well-known, and several clinical studies have shown significant benefits to humans. Therefore, this study aimed to assess the effects of various ratios of sorghum and tempeh flour (5:1, 2:1, and 1:1) on physicochemical and sensory characteristics of the flakes. The viability of Lactiplantibacillus plantarum subsp. plantarum Dad-13 in an instant cereal beverage was examined for 56 days at three distinct storage temperature, i.e 20, 30, and 37 °C. The 2:1 sorghum: tempeh flour ratio formulation was the most widely accepted. According to chemical analyses, all probiotic instant cereal drink formulations have the potential to be sources of fiber (6.4–10.6 g/100 g) and proteins (14.5–16.3 g/100 g). Furthermore, the probiotic instant cereal drink contains more fiber and protein than a commercial product. This product has a minimum viable count of probiotic bacteria > 6.0 log CFU/g, which is substantial enough to have positive health effects on Indonesian school-age children.